2020
DOI: 10.2147/copd.s260735
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Exertional Ventilatory Parameters Using Oscillometry in COPD</p>

Abstract: Background: Oscillometry is a tool to measure respiratory impedance that requires minimal patients' effort. In patients with chronic obstructive pulmonary disease (COPD), the correlation of respiratory impedance at rest with exertional ventilatory parameters, including exercise tolerance, has scarcely been reported. In addition, the utility of oscillometric parameters might differ between the inspiratory and expiratory phases due to airflow obstruction during expiration, but the hypothesis had not been validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…These results also reflect Zeng et al, 28 who recently found correlations between resistive and reactive parameters with 6MWD in COPD. They are also in line with that obtained by Yamamoto et al 45 The authors observed that oscillometric parameters correlated with exertional ventilatory parameters and reflected exercise tolerance in COPD subjects during cycle ergometer tests. Similar results were also observed in adults with sickle cell anemia, analyzing the correlations among 6MWD and oscillometric parameters.…”
Section: Discussionsupporting
confidence: 92%
“…These results also reflect Zeng et al, 28 who recently found correlations between resistive and reactive parameters with 6MWD in COPD. They are also in line with that obtained by Yamamoto et al 45 The authors observed that oscillometric parameters correlated with exertional ventilatory parameters and reflected exercise tolerance in COPD subjects during cycle ergometer tests. Similar results were also observed in adults with sickle cell anemia, analyzing the correlations among 6MWD and oscillometric parameters.…”
Section: Discussionsupporting
confidence: 92%
“… 64 The results are also consistent with that obtained recently using the 6-minute walking distance 65 , 66 and during cycle ergometer tests. 67 These associations agree with the involved physiology, describing an increase in ADL-Glittre test time with airway obstruction and Cdyn reduction. This reflects the systemic effects due to lung abnormalities, including the presence of airflow limitation and dynamic hyperinflation.…”
Section: Discussionsupporting
confidence: 81%
“…1b). The severity of COPD predicted by %FEV 1 is also related to the decrease of exercise tolerance, and Yamamoto et al reported that V O2 at peak exercise was significantly higher in COPD patients in GOLD stages I and II than in those in GOLD stages III and IV 14 . The current results also showed that the level of V O2 at peak exercise tended to be decreased depending on the GOLD stage, except for stage I (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing exercise tolerance, normally measured by the 6-minute walk test or cardiopulmonary exercise testing (CPET), is one of the important clinical features related to a poor prognosis in COPD patients 3,9,10 , and with CPET one can evaluate exercise tolerance with exertional ventilatory parameters precisely and safely 11,12 . For example, oxygen uptake (V O2 ) at peak exercise, which represents exercise tolerance, is significantly correlated with FEV 1 and %FEV 1 reflecting the severity of COPD 13,14 . Notably, with CPET, one can detect physical problems including cardiac dysfunction and functional skeletal muscle disorders during the test, which contributes to rapid initiation of treatment 15 .…”
Section: Introductionmentioning
confidence: 99%